Gangguan Rasa Nyaman Nyeri Gout Arthritis Menggunakan Metode Kompres Air Hangat - Nindi, Engryne; Luminda, Magdalena (JURNAL ILMIAH KESEHATAN MANADO, 2025)
such as the onset of various diseases increases the number of uric acid levels. The impact of arthritis gout pain can be caused in the elderly in the form of a decrease in the quality of life of the elderly because the pain is very disruptive to daily activities. It is necessary to manage non-pharmacological therapies to reduce joint pain, one of which is to provide warm compresses. Warm water compress therapy where the heat from a small towel that moves into the body, will make the blood vessels dilate and contract. Reduce or eliminate arousal by reducing muscle tension due to pain. The purpose of this scientific paper is the implementation of nursing care for Mrs. A.M with Problems of Discomfort Disorder of Gout Pain Arthritis using the warm water compression method at the Ranomuut Peace Home. The results of the study with the application of evidence based nursing of providing warm water compresses with a reduction in arthritis gouth pain in Mrs. A.M which was carried out for 3 days, the results of the evaluation were found that the administration of warm water compresses was effective in reducing arthritis gouth pain in Mrs. A.M. Conclusion: this scientific paper showed a decrease in arthritis gouth pain in Mrs. A.M after being given a warm water compress. Suggestion: Hopefully, the results of this research can increase knowledge and be able to provide nursing care to clients with arthritis pain problems and be able to apply nursing interventions based on the Evidence Based Practice approach.